Approach to the sonographic evaluation of fetal ventriculomegaly at 11 to 14 weeks gestation. Issue 1 (December 2016) - Manegold-Brauer, Gwendolin; Oseledchyk, Anton; Floeck, Anne; Berg, Christoph; Gembruch, Ulrich; Geipel, Annegret
Abstract Background The aim of the study was to report the prevalence and associated findings of fetal ventriculomegaly between 11 + 0 and 13 + 6 gestational weeks and to evaluate a sonographic approach to classify first trimester ventriculomegaly in the standard axial plane used for biparietal diameter (BPD) measurement. Methods The ratio between choroid plexus and lateral ventricle diameter (PDVDR), between the choroid plexus and lateral ventricle length (PLVLR) and between the choroid plexus and lateral ventricle area (PAVAR) were calculated from stored 2D images of the axial head plane in 100 normal fetuses and 17 fetuses with ventriculomegaly. Results The PDVDR, the PLVLR and the PAVAR were below the 5th percentile in 82.4 %, 94.1 % and 94.1 % of the cases with ventriculomegaly. Ventriculomegaly was isolated in 29.4 % and associated with further anomalies in 70.6 % at the initial evaluation. The mean PLVLR in euploid compared to aneuploid fetuses was significantly lower (0.40 versus 0.53 (p = 0.0332)). Conclusions The measurements of PDVDR, PLVLR and PAVAR are helpful to objectify ventriculomegaly at 11–14 gestational weeks. The PLVLR and PAVAR were superior to PDVDR, since there seems to be rather shrinkage of the choroid plexus than an increased width of the lateral ventricles in the first trimester.